2002
DOI: 10.1645/0022-3395(2002)088[1222:cmigsf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Corynosoma Magdaleni in Gray Seals From the Gulf of Bothnia, With Emended Descriptions of Corynosoma Strumosum and Corynosoma Magdaleni

Abstract: Because of the likelihood that Corynosoma magdaleni Montreuil, 1958. has been confused with C. strumosum (Rudolphi, 1802) in reports of parasites from seals and to clarify its distribution in the Baltic Sea, acanthocephalans from 26 young gray seals from the southwestern Finnish archipelago (western Baltic Sea) were examined. All harbored C. semerme (Forssell. 1904). In addition to C. semerme, 12 had both C. strumosum and C. magdaleni, 3 had only C. strumosum, and 9 had only C. magdaleni. Most anatomical struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 10 publications
4
39
0
Order By: Relevance
“…C. magdaleni was not reported again until Delyamure et al (1980) found it in 3 ringed seals from the Gulf of Finland, Baltic Sea. The subsequent reports of C. magdaleni were those of C. magdaleni adults in grey seals of SW Archipelago sea between the Gulf of Bothnia and the Baltic proper (Nickol et al 2002) and cystacanths in fishes of the Bothnian Bay and from the isolated land-locked ringed seal population of Lake Saimaa in SE Finland (Sinisalo et al , 2004. The present finding of C. magdaleni in ringed seals of the Bothnian Bay confirms the status of ringed seals as a genuine definitive host of C. magdaleni in the Baltic Sea, not only in the Lake Saimaa population where C. magdaleni is the only acanthocephalan species ever found (Sinisalo et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…C. magdaleni was not reported again until Delyamure et al (1980) found it in 3 ringed seals from the Gulf of Finland, Baltic Sea. The subsequent reports of C. magdaleni were those of C. magdaleni adults in grey seals of SW Archipelago sea between the Gulf of Bothnia and the Baltic proper (Nickol et al 2002) and cystacanths in fishes of the Bothnian Bay and from the isolated land-locked ringed seal population of Lake Saimaa in SE Finland (Sinisalo et al , 2004. The present finding of C. magdaleni in ringed seals of the Bothnian Bay confirms the status of ringed seals as a genuine definitive host of C. magdaleni in the Baltic Sea, not only in the Lake Saimaa population where C. magdaleni is the only acanthocephalan species ever found (Sinisalo et al , 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Until 1982 we identified specimens as either C. strumosum (Rudolphi, 1802) Lü he, 1904, or C. semerme (Forssell, 1904) Lü he, 1905 according to Petrochenko (1956). From 1988 onwards C. magdaleni were separated from C. strumosum following the descriptions later proposed by Nickol et al (2002). The worms were preserved in 70 % ethanol and cleared in lactophenol or they were studied from fresh slides illuminated from beneath.…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
See 3 more Smart Citations